They Say We Can’t Breathe Underwater - Wood, Natalie (UnderCurrents: Journal of Critical Environmental Studies, 2025)
This photo essay takes the reader through the images and ideas Wood explores in her solo exhibit, They Say We Can’t Breathe Underwater, installed at A Space Gallery in Toronto in September 2022. It incorporates photos of the artwork and installation, along with a discussion of the concepts floating through the exhibit. The images and this essay are found at the intersections of Abolition geographies, Black Radical Tradition, Black feminist, Black Atlantic, Aquatic theories.